Sound Localization Test in Presence of Noise (Sound Localization Test) in Adults without Hearing Alteration - Almeida,Gleide Viviani Maciel (2019)
Abstract Introduction Even people with normal hearing may have difficulties locating a sound source in unfavorable sound environments where competitive noise is intense. Objective To develop, describe, validate and establish the normality curve of the sound localization test. Method The sample consisted of 100 healthy subjects with normal hearing, > 18 years old,who agreed to participate in the study. The sound localization testwas applied after the subjects underwent a tonal audiometry exam. For this purpose, a calibrated free field test environment was set up. Then, 30 randompure tones were presented in 2 speakers placed at 45° (on the right and on the left sides of the subject), and the noise was presented froma 3rd speaker, placed at 180°. The noise was presented in 3 hearing situations: optimal listening condition (no noise), noise in relation to 0 dB, and noise in relation to - 10 dB. The subject was asked to point out the side where the pure tone was being perceived, even in the presence of noise. Results All of the 100 participants performed the test in an average time of 99 seconds. The average score was 21, the medium score was 23, and the standard deviation was 3.05. Conclusion The sound localization test proved to be easy to set-up and to apply. The results obtained in the validation of the test suggest that individuals with normal hearing should locate 70% of the presented stimuli. The test can constitute an important instrument in the measurement of noise interference in the ability to locate the sound.